On the possibilities of launching a regional pilot project for the development of a low-carbon economy in the Republic of Tatarstan - I. A. Makarov; E. E. Muzychenko (Georesursy)
Decarbonization is one of the main trends in global development of the last decade. More than 120 countries have already announced plans to achieve net-zero emissions by the middle of the century. Among them are Russia’s largest trading partners, including the European Union, China, Japan, the Republic of Korea, Kazakhstan, as well as the United States. These ambitions are supported by a tightening carbon regulation: carbon pricing has already been set up in 64 countries and regions. In the largest emissions trading system – the European one – carbon price has already exceeded 50 euros per ton of emissions.Significant effort in decarbonization has been taken in many industries (e.g., civil aviation, maritime transport, oil and gas industry), companies (which set up carbon neutrality targets and introduce internal carbon pricing) and the financial sector. Standards for corporate information disclosure about emissions and strategiesfor their reduction, in particular CDP andTCFD, are being developed and adopted.At the same time, ways to put pressure on competitors who do not want to bear the costs associated with reducing greenhouse gas emissions are being developed. For example, the Carbon Border Adjustment Mechanism (CBAM) will be launched by the European Union in 2023. All these trends mean that products with low carbon footprint become not just a competitive advantage for a company, but also an inevitable condition for its presence on the international market. Companies with a high carbon footprint face less favorable conditions of borrowing, as well as trading barriers and growing pressure from customers both corporate and individual.In this regard, the development of low-carbon economy in Russia is inevitable to minimize the costs associated with tightening regulation. It is becoming particularly relevant for export-oriented regions with large emissions, including the Republic of Tatarstan. In our opinion, the launch of a pilot project to regulate greenhouse gas emissions in this region is important not only for GHG reduction itself, but also for increasing competitiveness of Tatarstan companies on international markets and attracting investment from both Russian and foreign investors. In this paper, we explain the need to launch such a pilot and relying on the existing Russian and international experience on the one hand and taking into account the characteristics of Tatarstan’s economy on the other, we demonstrate a scheme by which such a project can be organized.